Cellular analysis of newly identified Hox downstream genes in Drosophila - Zhai, Zongzhao; Boy, Aurelia Lara; Lohmann, Ingrid (European journal of cell biology, 2010)
Hox genes code for conserved homeodomain transcription factors, which act as regional regulators for the specification of segmental identities along the anterior-posterior axis in all animals studied. They execute their function mainly through the activation or repression of their downstream genes. We have recently identified a large number of genes to be directly or indirectly targeted by Hox proteins through gene expression profiling in the model organism Drosophila. However, the cell-specific regulation of these downstream genes and the functional significance of the regulation are largely unknown. We have validated and functionally studied many of the newly identified downstream genes of the Hox proteins Deformed (Dfd) and Abdominal-B (Abd-B), and provide evidence that Hox proteins regulate a diverse group of downstream genes, from transcription factors to realisators with major and minor roles during morphogenesis.